Green Marketing and Green Practice Management in Culinary Tourism at Moksa Restaurant - Nurul Hakiki; Ni Kadek Surpi; I Gede Sutarya; I Dewa Ayu Hendrawaty Putri; I Ketut Pasek Wisuda (Jurnal Ilmiah Hospitality Management, 2026)
This study aims to analyze the integration of green marketing and green practice strategies with Balinese local wisdom values. A qualitative research approach was employed using a case study method, involving participatory observation, in-depth interviews, and documentation of restaurant operational activities. The findings reveal that green marketing at Moksa is implemented through ecological and spiritual communication strategies, fostering customer awareness and loyalty toward sustainability values. Green practices are reflected in the use of organic ingredients, renewable energy, a farm-to-table system, and circular waste management. The Tri Hita Karana philosophy serves as the ethical and cultural foundation for business operations, integrating spiritual harmony (Parahyangan), social balance (Pawongan), and environmental stewardship (Palemahan). This research offers theoretical implications by enriching the framework of green marketing based on local wisdom and provides practical and policy implications for the development of sustainable culinary tourism in Bali.